2021
DOI: 10.3390/su131810334
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Children in Story Co-Creation for Effective Serious Games

Abstract: Despite a growing interest in player-centred methods for serious games, little is known on how to achieve this goal in practice when prospective users are children. Foundational questions remain unanswered, such as to which design dimensions children should contribute, and how and when they should be engaged. This paper presents the methods and results of two studies that inspired Skies of Manawak, a game for developmental dyslexia remediation. The first study engaged 60 children (age 8–13) in 15 ideation work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 81 publications
(127 reference statements)
2
5
1
Order By: Relevance
“…When children have been involved in the design of game characters, there is a greater likelihood that as players, they will form linkages with these characters [6]. While the results of this pilot study showed that the Cosmic Sounds toolkit of codesigned games resulted in increased engagement (in line with findings from [52]) and a positive impact on the children's phonological awareness skills, specifically in the areas of consonant digraphs, vowel digraphs, syllabication, CVCe words, and a combination of all elements/skills, this study has limitations such as the sample size. The findings of this study are based on a semistructured interview with a DAI pedagogical expert and 15 children (although 20 children participated as codesigners).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…When children have been involved in the design of game characters, there is a greater likelihood that as players, they will form linkages with these characters [6]. While the results of this pilot study showed that the Cosmic Sounds toolkit of codesigned games resulted in increased engagement (in line with findings from [52]) and a positive impact on the children's phonological awareness skills, specifically in the areas of consonant digraphs, vowel digraphs, syllabication, CVCe words, and a combination of all elements/skills, this study has limitations such as the sample size. The findings of this study are based on a semistructured interview with a DAI pedagogical expert and 15 children (although 20 children participated as codesigners).…”
Section: Discussionsupporting
confidence: 73%
“…Studies show that GBL is one of a number of tools that can be used to enhance the learning process of children with dyslexia especially within the context of story, rewards, clear game goals, and objectives and feedback [15]. Furthermore, the incorporation of task-related activities in GBL assists in attention control in children with dyslexia [52]. GBL has many advantages for children with dyslexia, from the manner in which the content is presented (visual, text based, and aural) to the different learning situations, feedback, rewards, storyline, etc., which can motivate, and inspire them to learn [53].…”
Section: Introductionmentioning
confidence: 99%
“…Serious games have proven to be effective when used in various contexts because of their ability to teach, persuade, and entertain [33]. Their effectiveness has been measured through the experience of the players: their increase in literacy; raised awareness about the issue in focus; acquired skills and knowledge, etc.…”
Section: Evaluating Serious Gamesmentioning
confidence: 99%
“…However, while the importance of co-creation and co-design in serious game development is recognised, there has been a relative lack of focus on their potential to initiate such learning events. It is more known that, for example, co-design has been used to develop game concepts and the initial idea, but less so for the mechanics of the game, gameplay, and other aspects [15,[32][33][34][35]. The emphasis has primarily been on addressing usability and playability concerns rather than exploring the learning and experimentation opportunities that arise from participatory game design processes [7,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation